Improving Technology-Based Business Administration for Tour Guide of HPI Karimunjawa - Muhyadi; Siti Umi Khayatun Mardiyah; Arwan Nur Ramadhan (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
Community service activities aim at increasing the capabilities of HPI Karimunjawa members so that they are able to develop their potential to improve the welfare of tour guide entrepreneurs in the Karimunjawa Islands. The method used is the presentation of the concepts of administration and bookkeeping management, the concept of business and business administration systems, the concepts and strategies of business marketing, and the guided practice of assisting the filling of various business administration documents, and the practice and assistance of technology-based business administration management for HPI Karimunjawa using the online method. the job training and peer tutors. Based on the results of evaluations of the community service activities, it was found that: 97% of participants were able to explain the concepts of administrative management and bookkeeping able to master the material well, 85% of participants were able to explain the management of business and business administration systems well, and 97% were able to demonstrate the skills of marketing strategy management good business. Community service activities have been carried out properly in accordance with the planned program but to improve the use of technology it is necessary to improve the quality of internet network infrastructure in the Karimunjawa Islands.